Complications of central venous catheter insertion in a teaching hospital - Comerlato,Pedro Henrique (2017)
Summary Introduction: Central venous catheters are fundamental to daily clinical practice. This procedure is mainly performed by residents, often without supervision or structured training. Objective: To describe the characteristics of central venous catheterization and the complication rate related to it. Method: Retrospective cohort study. Adult patients undergoing central venous catheter insertion out of the intensive care unit (ICU) of a teaching hospital were selected from March 2014 to February 2015. Data were collected from medical charts using an electronic form. Clinical and laboratory characteristics from patients, procedure characteristics, and mechanical and infectious complications rates were assessed. Patients with and without complications were compared. Results: Three hundred and eleven (311) central venous catheterizations were evaluated. The main reasons to perform the procedure were lack of peripheral access, chemotherapy and sepsis. There were 20 mechanical complications (6% of procedures). Arterial puncture was the most common. Procedures performed in the second semester were associated with lower risk of complications (odds ratio 0.35 [95CI 0.12-0.98; p=0.037]). Thirty-five (35) catheter-related infection cases (11.1%) were reported. They were related to younger patients and procedures performed by residents with more than one year of training. Procedures performed after the first trimester had a lower chance of infection. Conclusion: These results show that the rate of mechanical complications of central venous puncture in our hospital is similar to the literature, but more attention should be given to infection prevention measures.